2003
DOI: 10.3141/1840-04
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Traffic Crash-Flow Relationships for Intersections: Dispersion Parameter, Functional Form, and Bayes Versus Empirical Bayes Methods

Abstract: Statistical relationships between traffic crashes and traffic flows at roadway intersections have been extensively modeled and evaluated in recent years. The underlying assumptions adopted in the popular models for intersections are challenged. First, the assumption that the dispersion parameter is a fixed parameter across sites and time periods is challenged. Second, the mathematical limitations of some functional forms used in these models, particularly their properties at the boundaries, are examined. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
191
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 320 publications
(208 citation statements)
references
References 14 publications
14
191
0
3
Order By: Relevance
“…Relatively early work on this topic is reported by Chapman (1972), Satterthwaite (1981), and Hauer et al (1988). Further development and continuation of the previous crash modeling research is reported by Bonneson and McCoy (1993), Belanger (1994), Maher and Summersgill (1996), Persaud and Nguyen (1998), Lord and Persaud (2000), Wang and Nihan (2004), Persaud et al (2002), and Miaou and Lord (2003). A main focus of prior studies has been to identify a defensible statistical relationship between crash counts and exposure.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Relatively early work on this topic is reported by Chapman (1972), Satterthwaite (1981), and Hauer et al (1988). Further development and continuation of the previous crash modeling research is reported by Bonneson and McCoy (1993), Belanger (1994), Maher and Summersgill (1996), Persaud and Nguyen (1998), Lord and Persaud (2000), Wang and Nihan (2004), Persaud et al (2002), and Miaou and Lord (2003). A main focus of prior studies has been to identify a defensible statistical relationship between crash counts and exposure.…”
Section: Introductionmentioning
confidence: 84%
“…While modeling urban intersection crashes using this func tional form for variance structure, Miaou and Lord (2003) found an improvement in model estimation. In addition they mentioned that treatment of dispersion parameter as a fixed parameter can seriously undermine the goodness of the estimate for individ ual sites by up to about 35%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is by far the most common prior within the standard NB model (e.g., Miaou and Lord, 2003). This prior has a spike near zero with a mean=1 and a large variance of 100.…”
Section: Simulation Designmentioning
confidence: 95%
“…Over-dispersion caused by unobserved heterogeneity in crash data is a serious problem and has been addressed in a variety of ways within the negative binomial (NB) modeling framework (Hauer, 2001;Heydecker and Wu, 2001;Miaou and Lord, 2003;Geedipally et al, 2009;Anastasopoulos and Mannering, 2009). However, the true factors that affect heterogeneity are often unknown to researchers and failure to accommodate such heterogeneity in the model can undermine the validity of the empirical results.…”
Section: Introductionmentioning
confidence: 99%